Quality of life of young adults with non-paraphilic problematic sexual behaviors: An exploratory study - Austin W. Blum; Samuel R. Chamberlain; Jon E. Grant (Addictive Behaviors Reports, 2018)
Introduction: Many young adults are unable to control their sexual behavior despite distress or negative consequences created by these activities—a clinical phenomenon described as non-paraphilic problematic sexual behavior (PSB). Little is known about clinical features associated with quality of life in PSB. Methods: 54 participants affected by PSB (ages 18–29 years) were recruited for a study on impulsivity in young adults. PSB was defined as the experience of sexual urges, fantasies, or behaviors that feel overwhelming or out of control. Participants were assessed using the Quality of Life Inventory (QOLI), other validated instruments, and questions examining aspects of health and well-being. Clinical measures associated with variation in quality of life were identified using the statistical technique of partial least squares (PLS). Results: Lower quality of life in PSB was associated with greater behavioral and self-report measures of impulsivity (specifically, Barratt attentional impulsiveness, lower age at first alcohol use), emotional dysregulation, problematic use of the internet, current suicidality, higher state anxiety and depression, and lower self-esteem. Conclusions: Impulsivity and affective problems are correlated with lower quality of life in PSB. These associations may provide a means to distinguish PSB from healthy sexual behavior. Keywords: Compulsivity, Hypersexuality, Impulsivity, Sexual behavior, Young adult